CONSISTENCY WITH CAPITAL MANAGEMENT IN NASARI SYARI’AH SAVING AND LOAN COOPERATIVES - Mohd. Heikal; Muti Miftahul Jannah; Muhammad Hafidz Akbar; Ariana Hasibuan; Indah Anta Sari; Lifia Suci Ramadani; Ahmad Faisal Pasaribu (Journal of Accounting Research, Utility Finance and Digital Assets, 2023)
The Savings and Loans Cooperative and Sharia Financing (KSPPS) is a microfinance institution that collects funds from the public and distributes them to people who need these funds. The purpose of this study was to determine the financial management system for sharia financing with a murabaha contract at KSPPS Nasari Syariah. This research is qualitative research using interview and documentation methods and obtained the results of primary and secondary data. The results of research on working capital management by increasing business show that capital management for KSP Nasari Syariah is 96.27%. This coefficient level indicates that capital management has a strong influence on business improvement at KSP Nasari Syariah.